Comparison of Cumulative Live Birth Rate (CLBR) According to Patient Oriented Strategies Encompassing Individualized Oocyte Number (POSEIDON) Stratification Among Low Prognosis Women Undergoing IVF-ICSI Cycles - R Bansiwal; R Mahey; N Malhotra; N Singh; M Saini; A Bhatt; N Nilima; Kh Mani; R Cheluvaraju; M Rajput; N Bhatla (JRI, 2023)
Background: The purpose of the current study was to evaluate patient-oriented strategies encompassing individualized oocyte number (POSEIDON) criteria, validate stratification of low prognosis women, and prognosticate their reproductive potential in terms of cumulative live birth rate (CLBR) in Indian women. Methods: Out of 4048 women who underwent IVF/ICSI, 3287 women met the criteria for final evaluation of CLBR. They criteria were divided into (a) group 1a as cases with <4 oocytes retrieved and 1b with 4-9 oocytes retrieved; (b) group 2a as cases with <4 oocytes retrieved and 2b with 4-9 oocytes retrieved; (c) group 3 (<35 years, AMH <1.2 ng/ml, AFC <5); and (d) group 4 (≥35 years, AMH <1.2 ng/ml, AFC <5). Non-POSEIDON group was sub-divided into normo-responders (10-20 oocytes) and hyper-responder (>20 oocytes). Results: Overall CLBR was two-fold lower in POSEIDON group as compared to non-POSEIDON group (p<0.001). For every one-year increase in the age, the odds of CLBR decreased by 4% (OR 0.96, CI 0.93-0.99) in POSEIDON group and by 5% (OR 0.95, CI 0.92-0.98) in non-POSEIDON group. For every unit increase in number of oocytes retrieved, the odds of CLBR increased by 1.22 times (OR1.22, CI 1.16-1.28) in POSEIDON group and by 1.08 times (OR 1.08, CI 1.05-1.11) in non-POSEIDON group. Among POSEIDON groups, the highest values in CLBR belonged to group 1b followed by 3, 2b, 4, 1a, and 2a. Conclusion: POSEIDON stratification of low-prognosis women undergoing IVF may be considered valid to prognosticate and counsel women undergoing IVF. Prospective studies will strengthen its validity among different ethnic populations.